Dulcinea in the writing of Juan José Arreola: reception, intertexuality and gender perspective - Verdín Padilla, Paulo César; Hermosillo Núñez, Perla Cristal (Anales de Literatura Hispanoamericana, 2021)
In this work the minifiction "Theory of Dulcinea", written by Juan José Arreola, is used to analyze the reception of the Cervantes character alluded to in the title, from the literary discourse, the intertextual field and the gender perspective. In the study, the considerations of Wolfang Iser, reception theorist and gender scholars Marcela Lagarde, Celia Amorós and Lucía Guerra are used. The methodological approach is carried out based on the narratological method proposed by Zavala. The conclusions of the analysis point to the female character in an erotic and sensual facet, a Dulcinea different from those found in Don Quixote, which works like the proposal of the author of the minifiction. Likewise, it emphasizes the fragmentation of women and their subordination to men, in addition to complying with the stereotype of weakness, submission, inferiority and impurity and the masculine figure with strength, superiority and intellectuality.
Keywords: minifiction; reception; intertextuality; gender perspective